Reducing Distortions To Agricultural Incentives : Progress, Pitfalls, And Prospects - Anderson, Kym, 1950- 1950- (The World Bank, 2006)
Most of the world's poorest people depend on farming for their livelihood. Earnings from farming in low-income countries are depressed partly due to a pro-urban bias in own-country policies, and partly because richer countries (including some developing countries) favor their farmers with import barriers and subsidies. Both sets of policies reduce national and global economic growth and add to inequality and poverty in developing countries. Acknowledgement of that since the 1980s has given rise to greater pressures for reform, both internal and external. Over the past two decades numerous developing country governments have reduced their sectoral and trade policy distortions, while many high-income countries continue with protectionist policies that harm developing country exports of farm products. Recent research suggests that the agricultural protectionist policies of high-income countries reduce welfare in many developing countries. Most of those studies also suggest that full global liberalization of merchandise trade would raise value added in agriculture in developing country regions, and that much of the benefit from global reform would come not just from reform in high-income countries but also from liberalization among developing countries, including in many cases own-country reform. These findings raise three key questions that are addressed in this paper: To what extent have the reforms of the past two decades succeeded in reducing distortions to agricultural incentives? Do current policy distortions still discriminate against farmers in low-income countries? And what are the prospects for further reform in the next decade or so?